Carbonaceous materials for the electrochemical clean-up of wastewater - Norten, Fiona Hestbæk Tennant (2018)
Using carbon adsorbents is the most common method of removing waste organics from water. However, the question remains of what to do with the carbon after adsorption. Landfill or incineration come with the obvious environmental consequences, and thermal regeneration is energetically costly and can be wasteful. The wastewater management company Arvia have developed a process for using electrochemical regeneration as an alternative. This thesis has examined that process in detail, in particular the role of the specific granular activated carbon used (Nyex).